2015
DOI: 10.1007/s00223-015-9998-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-Times-Weekly Administration of Teriparatide Improves Vertebral and Peripheral Bone Density, Microarchitecture, and Mechanical Properties Without Accelerating Bone Resorption in Ovariectomized Rats

Abstract: Daily and weekly administration of teriparatide (PTH1–34) reduces the risk of osteoporotic bone fractures. However, their effects on markers of bone formation and bone resorption differ. These results indicate that the dosing frequency of teriparatide may affect bone metabolism and bone structure, with different effects on bone strength. In the present study, to evaluate the dose-related effects of a low administration frequency of teriparatide on bone status, we investigated the effects of three-times-weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
1
25
2
Order By: Relevance
“…23–25 In this model, a significant reduction in the BMD in the OVX group compared with that in the sham group is observed starting from 3 months after the surgery. 23,36–39 This study monitored blood and urine samples until 7 weeks after surgery (4 weeks after the initial TPTD treatment), and dissected specimens at 7 weeks after the surgery for morphological evaluations to observe the early pharmacological actions of TPTD, especially on changes in the microarchitecture. In fact, we did not observe significant differences in the BMD, mechanical properties, average serum OC, or average cortical porosity between the sham group and OVX vehicle group, which is consistent with our previous report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23–25 In this model, a significant reduction in the BMD in the OVX group compared with that in the sham group is observed starting from 3 months after the surgery. 23,36–39 This study monitored blood and urine samples until 7 weeks after surgery (4 weeks after the initial TPTD treatment), and dissected specimens at 7 weeks after the surgery for morphological evaluations to observe the early pharmacological actions of TPTD, especially on changes in the microarchitecture. In fact, we did not observe significant differences in the BMD, mechanical properties, average serum OC, or average cortical porosity between the sham group and OVX vehicle group, which is consistent with our previous report.…”
Section: Discussionmentioning
confidence: 99%
“…23,26 For the sham surgery, ~10-mm-long incisions were made on the back of each rat, as in the ovariectomy, and the ovaries were exposed and then replaced.…”
Section: Methodsmentioning
confidence: 99%
“…; Takao‐Kawabata et al. ). Under some conditions, PTH(1‐34) can be used to improve fracture healing (Chiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…PTH(1-34), also known as Teriparatide, is an FDA-approved anabolic drug for osteoporosis, increasing bone deposition. It has also been demonstrated that, although PTH(1-34) can also stimulate bone resorption, the net effect of intermittent daily administration is the increase in bone mass (Hock & Gera, 1992;Burr et al 2001;Oswald et al 2014;Saidak et al 2014;Takao-Kawabata et al 2015). Under some conditions, PTH(1-34) can be used to improve fracture healing (Chiang et al 2013), although this may be dependent on the severity and location of bone injury as well as on an individual's overall bone health.…”
Section: Introductionmentioning
confidence: 99%
“…Common structural indices used in studies of PTH include trabecular number and thickness for cancellous bone, and cortical bone ratio and thickness for cortical bone structure . Common derived dynamic indices in clinical studies include mineralizing surface to assess the extent of surface active in mineralization at a particular time, mineral apposition rate, and bone formation rate .…”
Section: Effect Of Pth Dosing Interval On Mechanistic and Clinical Pamentioning
confidence: 99%